A Magnetically Separable Catalyst for Synthesis of 1‐Phenoxy‐2‐propanol Via Atom‐economic Reaction. Issue 10 (25th July 2014) - Feng, Shide; Cao, Fengyun; Lu, Bin; Cai, Qinghai
Abstract A magnetically separable catalyst Al2O3‐MgO/Fe3O4 was prepared by Al2O3‐MgO supported on magnetic oxide Fe3O4 and charactered by FT‐IR, XRD and SEM. The mixed oxides afforded high catalytic activity and selectivity for synthesis of 1‐phenoxy‐2‐propanol from phenol and propylene oxide with 80.3% conversion and 88.1% selectivity to 1‐phenoxy‐2‐propanol. Especially, facile separation of the catalyst by a magnet was obtained and the catalytic performance of the recovered catalyst was unaffected even at the forth run.